Effects of hydroxyl content in pure silica optical fiber exposed to kGy electron beams - Oresegun, A.; Zubair, H.T.; Ghassan, L.; Abdul-Rashid, H. A.; Hashim, S. A.; Bradley, D.A. * (Elsevier, 2021)
We present a study on the effect of high dose (kGy) electron beams on pure silica core fibers through examining the following phenomena within the fibers: radioluminescence (RL), radiation induced attenuation (RIA), and recovery. The objective is to identify the relevant characteristics of these fibers having favourable radiation response, that can be utilized in the development of dose measurement systems for high dose (kGy) environments. Two types of 20 m long pure silica optical fiber samples have been used, differing in their concentrations of hydroxyl (OH) content. Segments of 3.5 m length from each fiber were wound into coils of radius ~25 cm and exposed to consecutive irradiation doses, in the order of tens of kGy (10 kGy through 70 kGy in individual exposures), leading to a cumulative dose of some 300 kGy. The low-OH fiber showed saturation of response at the shorter wavelengths of the RL spectrum for doses of 30 kGy and above, resulting from presence of Oxygen Defect Centers (ODC). At the longer wavelengths the RL response of the low-OH optical fibers is observed to increase with dose, attributed to various bonding structural defects of silica nanoclusters. The saturation effect at shorter wavelengths is less prominent in the high-OH samples, where a monotonic increase is observed up to ~60 kGy indicating the formation of radiation induced ODC beyond this point. For cumulative dose of ~70 kGy, the highest RIA losses were registered at 550 nm (12.74 dB/m) for low-OH sample, and at 460 nm (4.75 dB/m) for high-OH sample. The high-OH sample showed much faster recovery post-irradiation, making it more suitable for repeated usage. Both the RL and RIA phenomena observed herein show the feasibility of pure silica optical fibers for dose measurement in high dose (kGy) environments up to individual dose of ~70 kGy.